2023
DOI: 10.7759/cureus.34202
|View full text |Cite
|
Sign up to set email alerts
|

Calcified Right Atrial Thrombus With Near-Systemic Pulmonary Pressures in a Morbidly Obese Patient: A Clinical Conundrum

Abstract: Intracardiac masses are not uncommon, but a calcified right atrial thrombus (CRAT) is an exceedingly rare entity and often poses a diagnostic and therapeutic dilemma. We discuss the case of an incidentally noted CcRAT in a 40-year-old man presenting with progressive dyspnea. We further review the literature on the subject, highlighting the need for an individual patient-centred care plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Sometimes large left atrial myxoma exhibits a wrecking motion across the mitral valve and behaves like a ball valve thrombus [ 5 ]. Although calcified right atrial ball valve thrombus has been reported in morbid obesity [ 6 ], left atrial ball valve thrombus has not been reported so far. The described case of isolated right atrial ball valve thrombus had severe pulmonary artery hypertension with right ventricular diastolic failure which was the predisposing factor for the formation of right atrial ball valve thrombus [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes large left atrial myxoma exhibits a wrecking motion across the mitral valve and behaves like a ball valve thrombus [ 5 ]. Although calcified right atrial ball valve thrombus has been reported in morbid obesity [ 6 ], left atrial ball valve thrombus has not been reported so far. The described case of isolated right atrial ball valve thrombus had severe pulmonary artery hypertension with right ventricular diastolic failure which was the predisposing factor for the formation of right atrial ball valve thrombus [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although calcified right atrial ball valve thrombus has been reported in morbid obesity [ 6 ], left atrial ball valve thrombus has not been reported so far. The described case of isolated right atrial ball valve thrombus had severe pulmonary artery hypertension with right ventricular diastolic failure which was the predisposing factor for the formation of right atrial ball valve thrombus [ 6 ]. Dyslipidemia in obesity produces endothelial dysfunction [ 7 ] which predisposes to thrombosis in the left atrium or left atrial appendage and may be the plausible cause for the formation of such a large malignant clot inside the left atrium.…”
Section: Discussionmentioning
confidence: 99%